Socio-Cultural Influence on Early Breastfeeding Initiation: Systematic Literature Review - Yanti, Eka Safitri (JURNAL IBU DAN ANAK, 2025)
This systematic literature review explores the sociocultural factors influencing Early Initiation of Breastfeeding (EIBF) and identifies effective culturally based interventions. Using PRISMA guidelines, ten studies published between 2015–2025 were analyzed thematically. Four key themes emerged: cultural beliefs significantly shape breastfeeding behaviors; weak health systems and limited staff training hinder EIBF; family and workplace support empower mothers; and culturally sensitive, community-based education improves outcomes. The findings highlight the need for cross-sectoral, culturally adaptive strategies to improve EIBF coverage in developing countries.